AKTIVITAS ANTIOBESITAS DAN ANTIINFLAMASI EKSTRAK ETANOL DAUN KATUK (Sauropus androgynus (L.) Merr) PADA TIKUS WISTAR JANTAN OBESITAS - Aulia Nurfazri Istiqomah; Hendra Mahakam Putra; Widhya Aligita; Betti Risa O (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Obesity is currently a disease with a prevalence that continues to increase every year and is a significant risk factor for cardiovascular disease. The relationship between obesity and inflammation is characterized by increased levels of TNF- which triggers inflammation. This study was conducted to determine the activity of katuk (Sauropus androgynus (L.) Merr) leaves as anti-obesity and anti-inflammatory properties. The study was conducted with a preventive method on white male wistar rats aged 2-3 months and body weight of 180-200 g. The test animals were divided into 6 groups that were induced by high-fat and carbohydrate diets except the normal group and were measured for anti-obesity and anti-inflammatory parameters. The results showed that katuk (Sauropus androgynus (L.) Merr) leaves can maintain activity as an anti-obesity and anti-inflammatory in test rats. Katuk leaf ethanol extract at a dose of 300 mg/kgBW has an effective activity as an anti-obesity, while at a dose of 150 mg/kgBW it has an anti-inflammatory activity.